2003
DOI: 10.1074/jbc.m300376200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ribosomal p70S6 Kinase Activation by Granulocyte Macrophage Colony-stimulating Factor in Neutrophils

Abstract: We report here for the first time the detection of the ribosomal p70S6 kinase (p70S6K) in a hematopoietic cell, the neutrophil, and the stimulation of its enzymatic activity by granulocyte macrophage colony-stimulating factor (GM-CSF). GM-CSF modified the V max of the enzyme (from 7.2 to 20.5 pmol/min/mg) and induced a timeand dose-dependent phosphorylation on p70S6K residues Thr 389

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Rapamycin inhibited significant changes in p70S6K-Thr 389 phosphorylation, with the strongest inhibition detected at 15 min post-HFS. p70S6K activation is thought to additionally require prior phosphorylation of an ERK-dependent site (Thr 421 /Ser 424 ) located in the module IV region of the enzyme (41,42). We found that U0126, but not rapamycin, blocked phosphorylation of the ERK-site on p70S6K (Fig.…”
Section: Ltp Maintenance In the Dentate Gyrus Does Not Requirementioning
confidence: 61%
“…Rapamycin inhibited significant changes in p70S6K-Thr 389 phosphorylation, with the strongest inhibition detected at 15 min post-HFS. p70S6K activation is thought to additionally require prior phosphorylation of an ERK-dependent site (Thr 421 /Ser 424 ) located in the module IV region of the enzyme (41,42). We found that U0126, but not rapamycin, blocked phosphorylation of the ERK-site on p70S6K (Fig.…”
Section: Ltp Maintenance In the Dentate Gyrus Does Not Requirementioning
confidence: 61%
“…Thus, the specific effects of hVps34 on Thr 389 phosphorylation are consistent with a specific regulation of S6K1 phosphorylation by mTOR. We also examined phosphorylation of S6K1 at Thr 421 / Ser 424 , a putative Erk site (51). In control cells, we observed significant basal Thr 421 /Ser 424 phosphorylation, with a decrease in electrophoretic mobility of the phosphorylated protein upon insulin stimulation (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Phosphorylation of the Thr229 and Thr389 sites depends on the Akt pathway and Thr389 is phosphorylated by mTOR. Furthermore, phosphorylation of Thr389 requires phosphorylation of Thr421/Ser424 through the Erk pathway (Zhang et al, 2001;Lehman et al, 2003;Tsokas et al, 2007). Thus, p70S6k is activated by both the Akt and Erk pathways.…”
Section: 6mentioning
confidence: 97%